Impact of Socioeconomic Factors on Access to Advanced Prosthodontic Treatments Utilizing Digital Dentistry Technologies - Mahboob, Musa; Shahzad, Aamir; Naseem, Hina Naz; Khan, Azeem Gohar; Khurram, Maleeha; Akhtar, Fahmeed (Journal of Neonatal Surgery, 2025)
Objective: To examine the connection between socioeconomic factors and access to advanced prosthodontic procedures with digital dentistry. Methods: This study was a descriptive cross-sectional analytical study, which was carried out at the Department of Prosthodontics. The 150 people who participated in our sample have been recruited across the institution using the non-probability consecutive sampling. Data was collected using a semi-validated questionnaire that was structured and comprised of questions on demographic and socioeconomic factors (age, gender, education, occupation, income, and residence) and questions on awareness, access, and utilization of digital prosthodontic services. Data was analyzed by use of SPSS v.26, including the Shapiro-Wilk test of normality, Chi-square test of association, and stratification analysis to control the modification of effects. Results: The participants had an average age of 42.8 ± 11.6 years, and 56 and 44% were males and females, respectively. Sixty-one point three percent of the sampled respondents were aware of digital prosthodontic options, and only 32.7 percent had experienced such treatment. The use of digital prosthodontics was linked to significantly higher income (p = 0.001), graduate education (p = 0.018), workforce engagement (p = 0.047), and urban geography (p = 0.006). The cost also remained a great obstacle, with 74 percent saying they believe that the treatment is too expensive. Conclusion: Socioeconomic inequality has a significant effect on access to digital prosthodontic care. Although an increased consciousness of access issues and technology-based care exists, affordability, education, and geography tend to limit the capacity of people to receive the care.